The Association Between Serum Estradiol Levels on hCG Trigger Day and Live Birth Rates in Non-PCOS Patients: A Retrospective Cohort Study - Xu, Xiaoyuan; Yang, Aimin; Han, Yan; Wang, Wei; Hao, Guimin; Cui, Na (Frontiers in Endocrinology, 2022)
Abstract Objective: To analyze the impact of serum estradiol (E2) levels on the hCG trigger day in non-PCOS women with fresh embryo transfer on live birth rate (LBR). Design: Retrospective cohort study Methods: Analysis of 13,950 patients who have experienced fresh embryo transfer. The main outcome measurement was LBR. Multivariable regression analysis was performed to investigate associations between E2 level on hCG trigger day and LBR. Stratification analysis was performed for tests for effect modification by subgroup. Furthermore, two-piecewise linear regression model was established to find nonlinear relationships. Results: Multivariable regression analysis showed a significant effect of E2 levels on LBR on the day of hCG injection (OR 1.005, 95%CI 1.001, 1.008) adjusting for covariates. Stratification analysis showed that the LBR was positively associated with E2 level on hCG trigger day (OR 1.008, 95%CI 1.001, 1.015) in the subgroup of low AFC on hCG trigger day. Specifically, two-piecewise linear regression model showed there was a positive association (OR 1.022, 95%CI 1.009,1.035) between E2 level and live birth when the concentration of serum E2 level was lower than 20.56 (100pg/ml). However, there was no significant association between E2 level and live birth (OR 1.000, 95%CI 0.995, 1.004) when the concentration of E2 was beyond the inflection point. Conclusions: E2 levels on hCG trigger day were segmentally connected with LBR. In non-polycystic ovary syndrome patients, an appropriate range of E2 levels needs to be defined for better pregnancy outcomes.